Seasonal variation in haematological parameters in crossbred horses used for urban traction from lages, Sc, Brazil Variações sazonais dos parâmetros hematológicos de equinos mestiços usados para tração urbana em Lages, SC, Brasil - de Souza A.F.* (2018)
© 2018, Universidade Federal do Parana.The aim of this study was to evaluate the influence of seasons on the hematological profile in horses used for urban traction in the city of Lages, Brazil. Blood samples were collected of the twenty crossbreed horses used for urban traction in the city of Lages, Brazil, carried out in four different periods according to the seasons, for carrying out the hematological profile, plasma total protein (PTP) and plasma fibrinogen. PTP was determined by refractometry method and the determination of plasma fibrinogen by heat precipitation method. Climate variations, such as maximum and minimum temperature, relative humidity and rainfall index for each period were obtained through access to the Center of Environmental Resources Information and Hydrometeorology of Santa Catarina. All values found were within the reference values commonly used for equine specie. There was no significant difference throughout the seasons on the values of erythrogram, leukogram, neutrophil-lymphocyte ratio and PTP. The MCH and plasma fibrinogen were higher in summer and eosinophils had significantly higher values in winter followed by summer. The region of Lages presents marked seasonal fluctuations, and these have little influence on hematological characteristics in horses used for urban traction.© 2018, Universidade Federal do Parana.O objetivo deste estudo foi avaliar a influência das estações do ano sobre o perfil hematológico em cavalos utilizados para tração urbana na cidade de Lages, Brasil. Amostras de sangue foram coletadas de vinte equinos mestiços utilizados para tração urbana na cidade de Lages, Brasil, realizada em quatro períodos distintos de acordo com as estações do ano, para a realização do perfil hematológico, proteína plasmática total (PTP) e fibrinogênio plasma. PTP foi determinada pelo método de refractometria e a determinação de fibrinogênio plasmático pelo método de precipitação pelo calor. As variações climáticas, como temperatura mínima e máxima, umidade relativa do ar e índice de pluviosidade de cada período foram obtidas por meio de acesso ao Centro de informações de Recursos Ambientais e Hidrometeorologia de Santa Catarina. Todos os valores encontrados estiveram dentro dos valores de referência comumente usados para a espécie equina. Não houve diferença significativa ao longo das estações sobre os valores do eritrograma, leucograma, relação neutrófilo:linfócito e na proteína total plasmática. Os valores de hemoglobina globular média e fibrinogênio plasmático foram maiores no verão e os eosinófilos apresentaram valores significativamente maiores no inverno seguido do verão. A região dos Campos de Lages apresenta flutuações sazonais bem demarcadas, e estas apresentam pouca influência nas características hematológicas nos equinos utilizados para tração urbana.